2021
DOI: 10.1039/d0en01033b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rhamnolipid biosurfactant on transport and retention of iron oxide nanoparticles in water-saturated quartz sand

Abstract: Column experiments and mathematical modeling results demonstrated that rhamnolipid biosurfactant can enhance the stability and mobility of iron oxide nanoparticles in water-saturated quartz sand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…Nanoparticle transport was described using MFT, an enhancement of clean-bed filtration theory, which has been shown to successfully simulate nanoparticle transport in a variety of porous medium systems. 36,41,42 Consistent with MFT, NP attachment/detachment was described using first-order kinetics 41…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticle transport was described using MFT, an enhancement of clean-bed filtration theory, which has been shown to successfully simulate nanoparticle transport in a variety of porous medium systems. 36,41,42 Consistent with MFT, NP attachment/detachment was described using first-order kinetics 41…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Two column experiments were performed using either 500 mg/L NaCl or synthetic brine solution to assess the mobility of PECNPs in 80–100 mesh OS sand following methods previously developed in our laboratory. , In brief, a borosilicate glass column (1 cm diameter × 15 cm length) was packed with clean 80–100 mesh OS under vibration and flushed with CO 2 gas for at least 60 min to facilitate the dissolution of entrapped gas during the water saturation process. Ten pore volumes (PVs) of the background solution were introduced into the column in an upflow mode using a high-performance liquid chromatography (HPLC) pump (ChromTech) to achieve complete water saturation of the packed column.…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned earlier, many factors affect the stability and formation of foam, e.g., the air entrapment in solution, the compositions and viscosity of the media, and the growth state of microbial cells [19,[22][23][24]. In order to discuss the relationships between foams and the key factors involved in foaming, the cell growth state, the air entrapment, and the properties of broth were investigated.…”
Section: The Relationships Between Foams and The Key Factors Involved...mentioning
confidence: 99%
“…There are two essential conditions for foam formation and stability: the external force and the property of solution [21]. Many factors affect the stability and formation of foams: the air entrapment in solution (e.g., gas flow rate and stirring frequency), the compositions and viscosity of media (e.g., pH, concentration of proteins and sugars, as well as presence of surfactant), the growth state of microbial cells (e.g., logarithmic phase, stable phase, and death phase), and the concentration of metabolites and surface-active substances (e.g., cresotic acid, rhamnolipid, and saponin) [19,[22][23][24]. The final foam volume depends on the complex interplay of four processes: bubble formation, bubble-atmosphere coalescence, bubble breakup into tiny bubbles, and bubble-bubble coalescence to increase bubble size [21].…”
Section: Introductionmentioning
confidence: 99%
“…[44][45][46][47] Recently, Liao and coworkers investigated the effects of rhamnolipid bio-surfactants on the mobility of iron oxide nanoparticles and silver nanoparticles in saturated porous media. 48,49 They found that the presence of rhamnolipid (5-50 mg L −1 ) enhanced the transport of silver nanoparticles due to rhamnolipid adsorption onto the surfaces of silver nanoparticles, which effectively slowed the oxidation, as well as adsorption of rhamnolipid onto sand surfaces, which competed for silver nanoparticle attachment sites. 49 Moreover, Zhao et al found that 0.1% saponins signicantly enhanced the secondary transport of Pseudomonas migulae AN-1 cells due to the decreased hydrophobicity of bacteria and quartz sand.…”
Section: Introductionmentioning
confidence: 99%